Renewable energy technologies in Asia: analysis of US patent data - Marinova, Dora (Curtin University of Technology, 2008)
The paper explores the link between patent trends and national innovation systems for aselection of Asian countries, namely China, India, Japan, Russia, South Korea andTaiwan, in the case of renewable energy. It uses 1975-2007 data from the US Patent andTrademark office. The concept of technological trajectory is also analysed suggesting thatwe are yet to witness an uptake in renewable energy. The imperatives of climate changehowever pose serious challenges to the world and in particular to the Asian countrieswhere most of the economic growth is likely to occur in the future. Japan is the dominantleader in foreign patenting in the US but renewable energy does not appear to be anational priority, as is also the case with South Korea, China and Taiwan. For Russia andIndia thou these technologies are emerging as an area of specialisation. All Asiancountries will need to strengthen their innovation systems in order to allow fortransformations towards a less fossil-fuel dependent global economy to occur.